Integration of Cannabis Extract Tetrahydrocannabinol:Cannabidiol in an Interdisciplinary Therapy Setting: A Case of Chronic Multilocular Pain Disorder - Tobias Romeyke; Rudolf Westfal (Medical Cannabis and Cannabinoids, 2022)
Multilocular pain syndromes with advanced chronification lead to a significant reduction in the quality of life of patients. The administration of cannabis is currently being discussed in the context of therapy-resistant pain and increasing opiate abuse. In this case study, possible side effects from the administration of a cannabis extract tetrahydrocannabinol:cannabidiol are examined. Furthermore, the effect on pain intensity and sleep quality is recorded. Due to numerous comorbidities in the patient, interactions with other medications are documented.